2018
DOI: 10.1177/1024907918765230
|View full text |Cite
|
Sign up to set email alerts
|

Osmangazi University score to reduce ionizing radiation in renal colic patients in emergency department

Abstract: Objective: Computerized tomography remains the gold standard imaging in renal colic patients. In this study, we develop a scoring system to select patients in emergency department for unnecessary computerized tomography imaging in order to decrease radiation exposure. Methods: Computerized tomography imaging of patients with renal colic in emergency department were retrospectively reviewed. Symptoms, laboratory results were recorded. Significant parameters were determined by univariate and multivariate analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Renal colic due to urinary stones is commonly seen in both the urology clinic and the emergency department, and often has a similar manifestation with LBP [ 6 ]. Nowadays, diagnosis of renal colic can be made with high accuracy by using CT [ 5 ]. In evaluating such patients, clinicians encounter many factors such as the requirement of providing the most accurate diagnosis, meeting patients’ expectations, radiation exposure, and the procedures’ cost covered by insurance companies, especially in developed countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Renal colic due to urinary stones is commonly seen in both the urology clinic and the emergency department, and often has a similar manifestation with LBP [ 6 ]. Nowadays, diagnosis of renal colic can be made with high accuracy by using CT [ 5 ]. In evaluating such patients, clinicians encounter many factors such as the requirement of providing the most accurate diagnosis, meeting patients’ expectations, radiation exposure, and the procedures’ cost covered by insurance companies, especially in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Fukuhara et al developed CHOKAAI (distension of kidney Capsule, Hydronephrosis, Occult blood in urine, Kidney stone history, Adult, Age, Diminution of pain within six hours) scoring system [ 10 ]. In 2018, Başeskioğlu et al designed the Osmangazi University Score, which used nausea, a history of stones, Cre, and hematuria [ 5 ]. In a meta-analysis that included the aforementioned scoring systems along with six others, Mirfazaelian et al found the STONE scoring system to be superior to others [ 1 , 19 - 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 studies sought to develop and validate prediction rules with the goal of predicting the likelihood that a patient with flank pain has ureterolithiasis (Table 6 in Supplement B). 24,30,32,[48][49][50][51][52][53][54][55][56][57][58] Of the 14 studies included, 1 was a 2019 meta-analysis that sought to assess the performance of existing prediction rules. The STONE score and the CHOKAI score were most frequently evaluated.…”
Section: Summary Of Current Evidencementioning
confidence: 99%